Association between corporate financial performance and corporate social responsibility in a crisis: focusing on the March 11 disaster / Masumi Nakashima and Saburo Ota. - Nakashima, Masumi; Ota, Saburo (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2016)
This study investigates how firms damaged by the Great East Japan Earthquake and Tsunami in 2011 (March 11 Disaster) proceeded toward a turnaround by focusing on corporate social responsibility (CSR). We define CSR as the responsibility that a firm has to pursue as a public institution for the benefit of the community and its environment. Ota and Nakashima (2015) proposed the Ota-Nakashima CSR model that measures CSR by applying the Ota turnaround model (2013) to the Kanji-Chopra CSR model. We compute CSR using the Ota and Nakashima CSR models (2015), and analyze the association between CSR and corporate financial performance (CFP). By examining the association between CSR and CFP, we investigate how firms damaged by the March 11 disaster consider planning and implementing CSR to proceed toward a turnaround.